Analisis Kualitas Desain Visual Akun Mobile Legends dengan Alight Motion terhadap Keputusan Pembelian Konsumen - Shapta Maulana Febriansyah; Wahyu Budi Priatna; Rici Tri Harpin Pranata; Sutisna Riyanto (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
The transformation of the Indonesian gaming industry, with the practice of buying and selling accounts worth billions of rupiah, has led to visual editing overcoming the limitations of conventional screenshots. This study aims to analyze the visual design quality of Mobile Legends accounts edited using Alight Motion and its influence on consumer purchasing decisions. A quantitative survey method was used, using a 5-point Likert scale questionnaire, with 38 respondents from a population of 60 consumers/resellers. The analysis results showed high visual design quality (mean 4.06) and high purchasing decisions (mean 3.92), with a significant effect (R² = 19.7%). The conclusion is that investing in visual editing can increase sales conversions.